LQR control for ball and beam system with deviated axis: simulation and experiment - Pham, Văn Chinh; Hoang, Duy Tân; Nguyen, Văn Đông Hải; Nguyen, Trung Dũng; Luong, Minh Đạt; Duong, Hoàng Nam; Ngo, Trần Minh Tú; Dang, Thái An (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The Ball and Beam system with Deviated Axis is a single input-multi output (SIMO) system commonly used in laboratories to test control algorithms. In this paper, we build and investigate an LQR controller in simulation. The controller demonstrates the ability to control the system balance in different placement positions. Next, we conduct a survey of the above controller in the object of the deflection bar through the control board STM32F4. Through simulation and experiment, our LQR controller has successfully controlled the system. In addition, the control parameters adjustment rules are also verified and summarized.